combine(8x-3)-(7x-4)+(-5x+6)=

Simple and best practice solution for combine(8x-3)-(7x-4)+(-5x+6)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for combine(8x-3)-(7x-4)+(-5x+6)= equation:


Simplifying
combine(8x + -3) + -1(7x + -4) + (-5x + 6) = 0

Reorder the terms:
bceimno(-3 + 8x) + -1(7x + -4) + (-5x + 6) = 0
(-3 * bceimno + 8x * bceimno) + -1(7x + -4) + (-5x + 6) = 0
(-3bceimno + 8bceimnox) + -1(7x + -4) + (-5x + 6) = 0

Reorder the terms:
-3bceimno + 8bceimnox + -1(-4 + 7x) + (-5x + 6) = 0
-3bceimno + 8bceimnox + (-4 * -1 + 7x * -1) + (-5x + 6) = 0
-3bceimno + 8bceimnox + (4 + -7x) + (-5x + 6) = 0

Reorder the terms:
-3bceimno + 8bceimnox + 4 + -7x + (6 + -5x) = 0

Remove parenthesis around (6 + -5x)
-3bceimno + 8bceimnox + 4 + -7x + 6 + -5x = 0

Reorder the terms:
4 + 6 + -3bceimno + 8bceimnox + -7x + -5x = 0

Combine like terms: 4 + 6 = 10
10 + -3bceimno + 8bceimnox + -7x + -5x = 0

Combine like terms: -7x + -5x = -12x
10 + -3bceimno + 8bceimnox + -12x = 0

Solving
10 + -3bceimno + 8bceimnox + -12x = 0

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + -3bceimno + 8bceimnox + -10 + -12x = 0 + -10

Reorder the terms:
10 + -10 + -3bceimno + 8bceimnox + -12x = 0 + -10

Combine like terms: 10 + -10 = 0
0 + -3bceimno + 8bceimnox + -12x = 0 + -10
-3bceimno + 8bceimnox + -12x = 0 + -10

Combine like terms: 0 + -10 = -10
-3bceimno + 8bceimnox + -12x = -10

Add '12x' to each side of the equation.
-3bceimno + 8bceimnox + -12x + 12x = -10 + 12x

Combine like terms: -12x + 12x = 0
-3bceimno + 8bceimnox + 0 = -10 + 12x
-3bceimno + 8bceimnox = -10 + 12x

Reorder the terms:
10 + -3bceimno + 8bceimnox + -12x = -10 + 12x + 10 + -12x

Reorder the terms:
10 + -3bceimno + 8bceimnox + -12x = -10 + 10 + 12x + -12x

Combine like terms: -10 + 10 = 0
10 + -3bceimno + 8bceimnox + -12x = 0 + 12x + -12x
10 + -3bceimno + 8bceimnox + -12x = 12x + -12x

Combine like terms: 12x + -12x = 0
10 + -3bceimno + 8bceimnox + -12x = 0

The solution to this equation could not be determined.

See similar equations:

| 3y-2y=1 | | 18=0.9(x-1) | | x+2x+4=21 | | -2/3s-1=56 | | 30=.666666667p | | 14T^2-3T-2=0 | | 2y^2-7y-1=0 | | 15-2y=20 | | 2x-16=180 | | X(12+x)=38 | | (7x-3)/(x-5)0 | | X^2+4x+4=2x+19 | | 0.75(2x-3)-.05(6-x)=1.5x+3 | | 3x+-1=5 | | (4t^3/7n^3)^4 | | 8z=11.2 | | 7-(4-x)=8 | | 3x+-1=-5 | | 4D^2-11D+7=0 | | 2x+1-(-2)-(-x)=2-2x | | R=5w-15 | | F(x)=2x^2+11x+12 | | A=(2x+1)(4x-3) | | 4(p+5)=5(p-7) | | -3m+23-2(m-1)=9m-(6m-8)-5m+2 | | 7-(x-4)=8 | | -(9z-(14z+4))=4+(4z+1) | | q-3r-s=p | | 3(2x+3)-10x=7-(8x-2) | | (1/5)^-1 | | Kw^2-13x-5=0 | | (x+3)(x+3)+289=0 |

Equations solver categories